Система індикаторів інформаційно-технологічного розвитку України - Полумієнко, С.К.; Рибаков, Л.О. (Екологічна безпека та природокористування, 2012)
The system ofindicatorsfor evaluation of thelevel of informationand technologicaldevelopment is considered. There are introduced IT Spread Index,Country Technology Advance Index, and the Country Information Defense Advance Index.The combination of theseindicesprovides a basis for the IT-industryanalysis and for the elaboration of its further development strategies.